2015
DOI: 10.1007/978-94-017-9993-5
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness and Health

Abstract: Long-term follow-up of patients treated for traumatic injury regarding physical and psychological function and health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(37 citation statements)
references
References 272 publications
(340 reference statements)
2
33
0
Order By: Relevance
“…A considerable amount of research interest has focused on the relationship between variables such as emotional competence and self-esteem, psychological well-being, mental health, and life satisfaction (Furr & Funder, 1998;Huebner, 1991;Montes-Berges & Augusto-Landa, 2014). Yet, over the past few years, we have seen that there is a lack of studies showing evidence of adolescents' self-perceived needs according to their socio-emotional development or Perceived emotional intelligence (PEI) (Toussaint et al, 2015). For this reason, it is necessary to carry out experimental studies in this field in order to see to what degree they support the theoretical models, which are not well understood.…”
Section: The Observation Of the Ei In Adolescentsmentioning
confidence: 99%
“…A considerable amount of research interest has focused on the relationship between variables such as emotional competence and self-esteem, psychological well-being, mental health, and life satisfaction (Furr & Funder, 1998;Huebner, 1991;Montes-Berges & Augusto-Landa, 2014). Yet, over the past few years, we have seen that there is a lack of studies showing evidence of adolescents' self-perceived needs according to their socio-emotional development or Perceived emotional intelligence (PEI) (Toussaint et al, 2015). For this reason, it is necessary to carry out experimental studies in this field in order to see to what degree they support the theoretical models, which are not well understood.…”
Section: The Observation Of the Ei In Adolescentsmentioning
confidence: 99%
“…Some studies focusing on the importance of personal factors in bullying have found their protective value against the development of internalizing (e.g., depression) and externalizing problems (e.g., suicide). For example, some authors suggest that forgiveness is an emotion-focused coping strategy to help victims alleviate the negative outcomes of being bullied (Freedman, 2018) and have lower levels of depression, anxiety, anger, or hostility (Toussaint et al, 2015). On the same vein other authors highlight other resources such as self-esteem (Turner et al, 2010), resilience (Sapouna and Wolke, 2013) and optimism (Rigby, 2003) as relevant factors that may successfully influence in overcoming victimization experiences.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, mother could experience more difficulty in giving forgiveness. Compared to fathers, mothers have massive susceptibility for experiencing psychological problem (Toussaint, Worthington, & Williams, 2015). This is because women, as compared to men, tend to react differently to conflicts related to psychological problems.…”
Section: A R T I C L E I N F O Abstractmentioning
confidence: 99%